Program Variety Show Dangdut Academy Asia 2 sebagai Alat Diplomasi Publik Indonesia - Intan Rizkia Futri; Dade Mahzuni; Nandang Rahmat (LP2M ISBI Bandung, 2018)
ABSTRACT Music as cultural diplomacy has been a subject of scholarly attention around the world. This research explores the subject within the Asia region. The purpose of this research is to describe the efforts in strengthening international diplomacy of Indonesia through dangdut music, namely Dangdut Academy Asia 2 TV program, throughout Asia specifically. Dangdut music which is originated from Indonesia gains a strong base of enthusiasts. The music genre has also established a niche market in the world of music. Popular culture and cultural diplomacy theories used in the research to explain how dangdut music which is formatted into a television variety show can positively affect the life of the society, nation, and state within Indonesia and throughout Asia. From this research, I found that the TV program has contributed in a very positive way to cultural diplomacy for Indonesia. This cultural diplomacy has been done through various cultural forms, including costumes, songs, foods, tourist attraction information, etc.Keywords: dangdut show, pop culture, cultural diplomacy, Dangdut Acadaemy Asia 2, variety show ABSTRAK Musik sebagai diplomasi budaya telah menjadi perhatian ilmiah di seluruh dunia. Penelitian ini juga mengeksplorasi subjek di wilayah Asia. Tujuan dari penelitian ini adalah untuk mendeskripsikan upaya Indonesia dalam memperkuat diplomasi internasional melalui musik dangdut, yaitu program TV Dangdut Academy Asia 2, yang ditayangkan khusus di Asia. Musik dangdut berasal dari Indonesia yang memiliki penggemar fanatik. Jenis musik ini telah membentuk pasar khusus di dunia musik. Teori budaya populer dan diplomasi budaya digunakan dalam penelitian ini untuk menjelaskan bagaimana musik dangdut yang dikemas menjadi program variety show televisi dapat secara positif memengaruhi kehidupan masyarakat, bangsa dan negara di Indonesia dan Asia.Dari penelitianini penulis menemukan bahwa program TV tersebut telah berkontribusi sebagai sarana diplomasi budaya Indonesia. Diplomasi budaya ini dilakukan melalui berbagai bentuk budaya yang tersaji dalam acara tersebut, seperti pakaian, lagu-lagu, makanan, informasi tempat wisata, dan lain-lain.Kata kunci: pertunjukandangdut, budaya pop, diplomasi budaya, Dangdut Academy Asia 2, variety show.